Middle power plays: How and when Mach middle managers use downward abuse and upward guanxi to gain and maintain power - Keng‐Highberger, Fong; Feng, Zhiyu; Yam, Kai Chi; Chen, Xiao‐Ping; Li, Hu (Journal of organizational behavior, 2024)
Summary Given Machiavellianism's strong historical and theoretical roots in power and politics, there are surprisingly few empirical studies, if any, that directly examine how Machiavellians attain and maintain power in organizations. Understanding this is important because Machiavellian employees have managed to effectively gain power to reach managerial positions of influence in organizations despite their negative reputation. Further, there are contradictory theories and peripheral empirical findings that suggest they gain power either by strategically forging important connections or through coercive force. We propose that a Mach middle manager perspective can help illuminate which power‐gaining strategy is used. Drawing from the Machiavellianism literature and power dependence theory, we theorize how Mach middle managers gain coercive power through abusive supervision on those with less power (their subordinates), while building close guanxi with those with more power (their senior manager) to obtain relational empowerment. Moreover, we theorize that they maintain power by increasing both power‐gaining strategies when Mach middle managers perceive a high threat to hierarchy from subordinates, suggesting these parallel relations are positively connected. We found support for our theoretical model using data from a multi‐confederate experimental lab study and two multi‐wave field studies. The theoretical and empirical implications of our findings are discussed.